(untitled) (Indian Journal of Nematology, 2024)
EDITORIAL BOARD Editor-in-Chief : DR. PANKAJ , Editor : DR. T.K. DUTIA MEMBERS PROF. QAMARMAJEED, Sokoto, Nigeria PROF. H.S. GAUR, Meerut PROF. IRSHAD MAHMOOD, Aligarh DR. KEITH G. DAVIES, UK DR. RICHARD SIKORA, Germany DR. BYRON ADAMS, USA DR. R.K. KAUL, Jodhpur DR. SJ EAPEN, Calicut DR.M. NAGESH, Shimla DR. S.S. HUSAINI, Bangalore DR. ANJU VERMA, USA DR. S.B. SHARMA, Australia DR. ALY KHAN, Pakistan DR. A.U. SIDDIQUI, Udaipur DR. K.K. KAUSHAL, New Delhi DR. A.H. WANI, Jammu DR. B.A. PATEL, Anand DR. R.K. WALIA, New Delhi DR. N.K DHILLON, Ludhiana